Including and Excluding Indigenous Religion through Law. - Årsheim, Helge (Numen: International Review for the History of Religions, 2018)
Across the world, indigenous peoples enjoy unprecedented access to international, regional, and domestic legal remedies to gain protections for their religious, spiritual, and customary identities, beliefs, and practices through a wide spectrum of judicial platforms. These remedies provide a broad, inclusive, and “intersectional” vocabulary for indigenous peoples to formulate their rights claims. Despite the growing interest in research on law and religion and the recognition that international human rights law is vital to the formulation of indigenous rights claims, the nature, scope, and effects of the proliferation of international norms protecting “indigenous religion” has so far not been subject to extensive research. Seeking to address this lacuna in the literature, this article explores the extent to which indigenous peoples involved in two recent Supreme Court decisions in Canada and Norway have chosen to rely on the available vocabulary for the formulation of rights claims related to “indigenous religion.”